The Generic Risks and the Potential of SDN-1 Applications in Crop Plants - Katharina Kawall (MDPI AG, 2021)
The use of site-directed nucleases (SDNs) in crop plants to alter market-oriented traits is expanding rapidly. At the same time, there is an on-going debate around the safety and regulation of crops altered with the site-directed nuclease 1 (SDN-1) technology. SDN-1 applications can be used to induce a variety of genetic alterations ranging from fairly ‘simple’ genetic alterations to complex changes in plant genomes using, for example, multiplexing approaches. The resulting plants can contain modified alleles and associated traits, which are either known or unknown in conventionally bred plants. The European Commission recently published a study on new genomic techniques suggesting an adaption of the current GMO legislation by emphasizing that targeted mutagenesis techniques can produce genomic alterations that can also be obtained by natural mutations or conventional breeding techniques. This review highlights the need for a case-specific risk assessment of crop plants derived from SDN-1 applications considering both the characteristics of the product and the process to ensure a high level of protection of human and animal health and the environment. The published literature on so-called market-oriented traits in crop plants altered with SDN-1 applications is analyzed here to determine the types of SDN-1 application in plants, and to reflect upon the complexity and the naturalness of such products. Furthermore, it demonstrates the potential of SDN-1 applications to induce complex alterations in plant genomes that are relevant to generic SDN-associated risks. In summary, it was found that nearly half of plants with so-called market-oriented traits contain complex genomic alterations induced by SDN-1 applications, which may also pose new types of risks. It further underscores the need for data on both the process and the end-product for a case-by-case risk assessment of plants derived from SDN-1 applications.